PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 011 TALANG GEDABU KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Muhammad Nor; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPS Elementary School fourth grade students Gedabu 011 Talang District of Kulim Rafts in the academic year 2014/2015. Subjects in this study were students in fourth grade Gedabu State 011 Talang District of Kulim Rafts Indragiri the number of students 22 students, consisting of 15 men and 7 women. This study is a Class Action Research (Classroom Actions Research) which comprises two cycles. Based on the results of research and data analysis known that an increase in the percentage of activity for teachers to get an average of 79.37% success criteria very well. Implementation of the second cycle of activities for teachers to get an average of 91.25% success criteria very well. Implementation of the first cycle of activity students gain an average of 73.12% success with both criteria. Implementation of the second cycle of activity students gain an average of 89.37% success criteria very well. before implementation of cooperative learning model type STAD was 65.59 from 22 people who follow replicates only 8 people were completely and 14 students have not completed the completeness percentage of 36.36% with less qualification. In the first cycle UH 1 daily value increased to 75.29 students who have increased as much as 14.78%, the number of students who completed 9 students. In the second cycle increased the average value of as much as 13.28% to 85.29. All students completed the implementation of the UH 2 with a percentage of 100%. Class declared complete when it reaches ≥ 80 of the number of students who reach the specified KKM is ≥ 70. It can be concluded that cooperative learning model Student Team Achievement Devision (STAD) can improve learning outcomes IPS Elementary School fourth grade students Gedabu 011 Talang District of Kulim raft.Keywords: Cooperative Learning Model Student Team Achievement Devision ( STAD ) , IPS Learning Outcomes